Corporate governance and its role in reducing the effects of creative accounting: a field study of a sample of Iraqi companies - Hatem Karim Kazem (Iraqi Journal for Administrative Sciences, 2025)
Aims of this Research to identify the role of Corporate Governance in limiting the effects of Creative Accounting Methods and through a field study of a sample of Iraqi Companies, and to achieve this goal researcher followed the style of Statistical Analysis using Questionnaire as a tool to collect data from individual sample consisting of Internal and External Auditors , The Staff of the Company and Analysts Financial, and research sample consists of (40) individual for the purpose of data analysis and Hypothesis testing was to depend on Statistical Program (SPSS). The research has come to a role for the Application of Corporate Governance Statistically significant at the level (5%) to reduce the effects of Creative Accounting Methods, as it showed the results of research that there is strong correlation between Corporate governance and Creative Accounting of (0.978) as well as a correlation slope between Governance Companies, Creative Accounting, amounting to ( = 1.085) , as well as The total coefficient of determination(R2) the amount of (0.956) This means that Corporate Governance is able to explain what percentage for (95.6%) of the changes in The Independent Variable (Creative Accounting), While the percentage the remaining (4.4%) is attributable to the contribution of other variables not included in the scope of this research. The research has come to a set of Conclusions including: The Corporate Governance role of large and effective in eliminating Administrative and Financial Practices misunderstandings and prevent any acts no Ethical and thus reduce the effects of Creative Accounting methods of manipulating the accounting numbers, and other cases of fraud and deception and the exploitation of legal loopholes and the multiplicity of accounting alternatives. . The most important Recommendations of the Search: The need for tough legislation to prevent the occurrence of fraud and corruption and all acts Professional non-moral in the reports and financial statements, as well as offer Education Programs and establish Seminars for users of Accounting Information and work to develop A Culture of Authority of Governance (Corporate Governance) through the establishment of Scientific Symposia and Workshops.